Réponses

2014-03-13T09:42:36+01:00
Bonjour,

a)  (3x + 7) + (3x + 5) = 0
3x + 7 + 3x + 5 = 0
6x + 11 = 0
6x = -11
x = -11/6

b)  (3x + 7)(3x + 5) = 0
3x + 7 = 0   ou   3x + 5 = 0
3x = -7   ou   3x = -5
x = -7/3   ou   x = -5/3

c) 25x² = 20x - 4
25x² - 20x + 4 = 0
(5x - 2)² = 0
5x - 2 = 0
5x = 2
x = 2/5

d)  (2x - 6)² = 4
(2x - 6)² - 4 = 0
(2x - 6)² - 2² = 0
[(2x - 6) - 2][(2x - 6) + 2] = 0
(2x - 6 - 2)(2x - 6 + 2) = 0
(2x - 8)(2x - 4) = 0
2x - 8 = 0   ou   2x - 4 = 0
2x = 8   ou   2x = 4
x = 8/2   ou   x = 4/2
x = 4   ou   x = 2

e)  (3x + 1)(2x - 5) - (2x - 5)² = 0 
(3x + 1)(2x - 5) - (2x - 5)(2x - 5) = 0
(2x - 5) [(3x + 1) - (2x - 5)] = 0
(2x - 5) (3x + 1 - 2x + 5) = 0
(2x - 5) (x + 6) = 0
2x - 5 = 0   ou  x + 6 = 0
2x = 5   ou  x = -6
x = 5/2   ou   x = -6